Functioning of Microsomal Cytochrome P450s: Murburn Concept Explains the Metabolism of Xenobiotics in Hepatocytes - Manoj, Kelath Murali; Parashar, Abhinav; Gade, Sudeep K.; Venkatachalam, Avanthika (Frontiers in Pharmacology, 2016)
Using oxygen and NADPH, the redox enzymes cytochrome P450 (CYP) and its reductase (CPR) work in tandem to carry out the phase I metabolism of a vast majority of drugs and xenobiotics. As per the prevailing paradigm, binding of substrate to CYP’s heme distal pocket allows CPR to pump electrons through a CPR-CYP complex. In turn, this is supposed to lead to the activation of oxygen at CYP’s heme-centre, giving a two-electron deficient enzyme reactive intermediate, Compound I. The formation of diffusible radicals and reactive oxygen species (DROS) was attributed to the heme-centre and it was considered to be an undesired side-reaction. Recently, we had challenged several perceptions and proposed the murburn (“mured burning” or “mild unrestricted burning”) concept to explain heme enzymes’ catalytic mechanism, electron-transfer phenomena and the regulation of redox equivalents’ consumption. Murburn concept incorporates a one-electron paradigm, advocating obligatory roles DROS. The new understanding does not call for high-affinity substrate-binding at the heme distal pocket of the CYP (the first and the most crucial step of the erstwhile catalytic paradigm) or CYP-CPR protein-protein complexations (the operational backbone of the erstwhile cycle). Herein, the dynamics of reduced nicotinamide nucleotides' consumption, peroxide formation and depletion, specific (and side) product formation was probed with various controls, by altering reaction variables and environments and through the incorporation of diverse probes. In several CYP systems, control reactions lacking the specific substrate showed comparable or higher peroxide in milieu, thereby discrediting the foundations of the erstwhile hypothesis. The profiles obtained by altering CYP:CPR ratios and the profound inhibitions observed upon the incorporation of catalytic amounts of horseradish peroxidase confirm the obligatory roles of DROS in milieu, ratifying murburn as the operative concept. The mechanism of uncoupling (peroxide and water formation) was found to be dependent on multiple one and two electron equilibriums amongst the reaction components. The investigation explains the evolutionary implications of xenobiotic metabolism, confirms the obligatory role of DROS in routine redox metabolism and establishes a hitherto unknown modality of rate enhancement for a redox enzyme like CYP.